Investigation of the cytotoxic effects of juglone on C6 glioma cell line - Bektas, Ekin; Kucak, Mine; Unlu Bektas, Firuze; Onturk, Tolga; Muslumanoglu, Muhammed Hamza (YILDIZ TECHNICAL UNIV, 2024)
Juglone is an organic compound found naturally in the leaves, roots, bark, and fruits of plants belonging to the Juglandaceae family. It has toxic and growth inhibiting features in many plant species. Glioma is a type of tumorigenesis that occurs when glial cells begin to proliferate uncontrollably because of various reasons. C6 glioma cell line is a tumour line derived from brain glial cells of Rattus norvegicus. In this study, after juglone application to C6 glioma cell line, MTT and WST-1 tests were performed and IC50 values were found 6.666 mu M and 5.646 mu M, respectively. The data obtained showed that the results of two tests were closely related and the cytotoxic effects of juglone were present in this cell line. Furthermore, colony formation assay showed a decrease in colony formation abilities of the cells after juglone treatment. These observations were reinforced by wound healing assay and similarly, the migration ability of the cells decreased with juglone application. Morphological examinations of the cell groups were performed under fluorescent microscopy by DAPI staining, which showed a reduction in cell number. As a final step, the expression levels on the cancer related genes were determined by RT-qPCR. While a significant increase was observed in the expression levels of pro-apoptotic genes compared to the control group, a significant decrease was observed in the expression of the anti-apoptotic gene and the gene involved in proliferation. In line with the data presented, the cytotoxic effects of juglone were determined in the C6 glioma cell line.
Keywords: Cancer; Cytotoxicity; Glioma; Juglone; RT-qPCR; GROWTH; PLUMBAGIN; MIGRATION; WALNUT; SYSTEM; Engineering